Achieving sustainable aquaculture: Historical and current perspectives and future needs and challenges - Claude E. Boyd; Louis R. D'Abramo; Brent D. Glencross; David C. Huyben; Lorenzo M. Juarez; George S. Lockwood; Aaron A. McNevin; Albert G. J. Tacon; Fabrice Teletchea; Joseph R. Tomasso Jr; Craig S. Tucker; Wagner C. Valenti (Wiley, 2025)
Important operational changes that have gradually been assimilated and new approaches that are developing as part of the movement toward sustainable intensive aquaculture production systems are presented via historical, current, and future perspectives. Improved environmental and economic sustainability based on increased efficiency of production continues to be realized. As a result, aquaculture continues to reduce its carbon footprint through reduced greenhouse gas emissions. Reduced use of freshwater and land resources per unit of production, improved feed management practices as well as increased knowledge of nutrient requirements, effective feed ingredients and additives, domestication of species, and new farming practices are now being applied or evaluated. Successful expansion into culture of marine species, both off and on shore, offers the potential of substantial increases in sustainable intensive aquaculture production combined with integrative efforts to increase efficiency will principally contribute to satisfying the increasing global demand for protein and food security needs.